Kegiatan ‘Mystery Box’ untuk Melihat Pemaknaan Kata ‘Anjing’ sebagai Bahasa Keseharian - Faridhian Anshari; Helencia Putri Permata Sari; Heni Suryani (Madani : Indonesian Journal of Civil Society, 2024)
The use of the word 'Anjing' (dog) as part of everyday language in Indonesia has undergone a cultural transformation. The word, originally defined as an animal, has shifted in meaning to become a term expressing a myriad of emotions, often used as a curse word. This social phenomenon is designed to capture the various interpretations of the word 'Anjing', both its original meaning (langue) and the meanings it has acquired over time (parole). This theme is significant in understanding the intentions behind the use of the word 'Anjing' in everyday language, whether it is used as an insult towards others or as a word devoid of meaning. The social activity employs an experimental method through the installation of an art exhibit called the 'mystery box', containing numerous writings related to the word 'Anjing', as well as audio and video displaying vocalizations of dogs. The results show that late adolescent and early adult subjects quickly interpret the word 'Anjing' as an insult. In contrast, early adolescent, late adult, and elderly subjects interpret 'Anjing' as an animal, without any tendency towards using it as an insult. This is supported by the use of different insults in the past and indicates the position of insults as cultural artifacts. Furthermore, the experiment serves as a reminder that each individual has a different interpretation of things, which cannot be imposed by others due to their differing experiences and knowledge.